Pgp3 protein of Chlamydia trachomatis inhibits apoptosis via HO-1 upregulation mediated by PI3K/Akt activation. (May 2023) - Shu, Mingyi; Bu, Jichang; Lei, Wenbo; Chen, Lili; Zhou, Zhou; Lu, Chunxue; Chen, Chaoqun; Li, Zhongyu
Abstract: As an obligate intracellular pathogen, Chlamydia trachomatis assumes various strategies to inhibit host cells apoptosis, thereby providing a suitable intracellular environment to ensure completion of the development cycle. In the current study, we revealed that Pgp3 protein, one of eight plasmid proteins of C. trachomatis that has been illustrated as the key virulence factor, increased HO-1 expression to suppress apoptosis, and downregulation of HO-1 with siRNA–HO–1 failed to exert anti-apoptosis activity of Pgp3 protein. Moreover, treatment of PI3K/Akt pathway inhibitor and Nrf2 inhibitor evidently reduced HO-1 expression and Nrf2 nuclear translocation was blocked by PI3K/Akt pathway inhibitor. These findings highlight that induction of HO-1 expression by Pgp3 protein is probably due to regulation of Nrf2 nuclear translocation activated by PI3K/Akt pathway, which provide clues on how C. trachomatis adjusts apoptosis. Highlights: Pgp3 protein up-regulated HO-1 expression to inhibit apoptosis. The activation of PI3K/Akt may trigger Nrf2 nuclear translocation subsequently leading to HO-1 increment.